JOINT ULTRASONOGRAPHY IN RHEUMATOID ARTHRITIS: PATHOGENETIC RATIONALE, POSSIBLE USE IN DIAGNOSIS, THERAPY EFFICIENCY EVALUATION, AND OUTCOME PREDICTION - O. G. Alekseeva (Научно-практическая ревматология)
Rheumatoid arthritis (RA) is an autoimmune rheumatic disease characterized by chronic erosive arthritis and systemic inflammatory changes, which lead to early disability and worse quality of life in patients. Current imaging techniques have become a new stage of not only in diagnosing, but also in assessing their course and in predicting outcomes. Joint ultrasonography in RA is now considered to be one of the available and widely used techniques. This review of literature provides a detailed analysis of publications on joint ultrasonography in RA. Their results are controversial and frequently cast any doubt on the informative value of this technique. The large number of original publications suggests that rheumatologists are taking a great interest in this method. The review gives the current points of view on the pathogenetic rationale, diagnostic value, and prognostic potential of using ultrasound in patients with RA. It discusses the issues of a methodology for diagnostic procedures, the need of using power Doppler imaging, and current semiquantitative inflammation rating scales. The review presents the existing guidelines for the use of ultrasound in RA, confirming the importance of this imaging technique.